Miasto Lida w historii i twórczości Aleksandra Jurewicza - Konczewska, Katarzyna (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The article is based on novels by Aleksander Jurewicz that are a source of information about old times and the everyday life of the Poles living in Lida as well as their culture and language. With regard to the peculiarities of the Polish language used by the inhabitants of Lida, the author presents her remarks on the phonetics, inflection, syntax, and vocabulary.